2020
DOI: 10.1210/clinem/dgaa887
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Indeterminate Thyroid Nodules Managed Nonoperatively after Molecular Testing

Abstract: Context Molecular testing to refine the diagnosis of cytologically indeterminate thyroid nodules has become increasingly popular, but data on long-term durability of test results and rate of delayed operation are limited. Objective Determine the delayed rate of surgical resection in indeterminate nodules with benign/negative molecular testing and the risk of false-negative molecular test results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Third, we do not have surveillance data for benign molecular test patients who may have experienced nodule progression that could have impacted QOL. However, based on our previous results from ultrasound surveillance over a median follow-up of 27 months, 84% of nodules remained stable in size and appearance, 28 therefore this variable is unlikely to significantly affect QOL outcomes observed in our study. Lastly, there was loss of patients during longititudinal follow-up, which may introduce nonresponse bias.…”
Section: Discussionmentioning
confidence: 63%
“…Third, we do not have surveillance data for benign molecular test patients who may have experienced nodule progression that could have impacted QOL. However, based on our previous results from ultrasound surveillance over a median follow-up of 27 months, 84% of nodules remained stable in size and appearance, 28 therefore this variable is unlikely to significantly affect QOL outcomes observed in our study. Lastly, there was loss of patients during longititudinal follow-up, which may introduce nonresponse bias.…”
Section: Discussionmentioning
confidence: 63%
“…Another limitation of this study is the inability to formally characterize patients with benign molecular testing who did not undergo surgery for confirmation of benignity. Up to a 6% false-negative rate has been reported in those with benign molecular testing, discovered by changes on serial ultrasound assessment longitudinally [ 29 ]. However, this is a limitation of all retrospective indeterminate thyroid FNA molecular studies, given surgery is avoided in all those with benign molecular test results.…”
Section: Discussionmentioning
confidence: 99%
“…An adult group detailed their use of next-generation sequencing in these lesions, noting the results led to safe, nonoperative surveillance in >80% of lesions and a four-fold increased rate of malignancy in resected nodules [69 ▪ ]. Another institutional study looked at molecular testing in both Bethesda III and IV lesions, and showed successful 3–4 years surveillance of those with benign testing, with about a 5% false negative rate for molecular testing [70]. In pediatric patients with Bethesda category III cytology, molecular testing showing a gene fusion (e.g.…”
Section: Molecular Testsmentioning
confidence: 99%